IMPROVING LEARNING ORGANIZATION AND PRACTICAL COMMUNITY THROUGH KNOWLEDGE MANAGEMENT - Sinaga, Dameria (Ikatan Dosen Menulis, 2024)
A learning organization is one of the popular concepts in management literature in the 1990's. Learning is a deliberate effort by someone to change behavior out of an interaction. The implications of the learning organization are collective learning, question and answer sessions. The manager expects colleagues are a part of a learning organization. Practice community is the combination of work and learning.